Upoštevanje vodila »Ne oživljaj.« - Kalender Smajlović, Sedina (Obzornik zdravstvene nege, 2024)
Introduction: The decision to stop active treatment includes the »Do Not Resuscitate« order. Research indicates that the nurse's role includes helping patients, families, members of the healthcare team to make informed decisions in relation to this order. The aim of this literature review was to explore nurses’ experiences and views regarding adherence to this order. Methods: An integrative literature search for studies published between 2012 and 2022 in the COBIB, CINAHL and PubMed databases using the keywords »vodilo Ne oživljaj.«, »medicinske sestre«, »do not resuscitate orders«, »nurses«. The literature search process is illustrated by the PRISMA diagram. Eighteen studies were included in the integrative review. The results of the studies reviewed were summarised and compared in terms of content.Results: Based on the analysis of the articles, three distinct categories were formulated: (1) factors related to nursing ethics, (2) nurses' demographic and professional factors, and (3) relational factors (family, society).Discussion and conclusion: The results show that issues related to life and death are influenced by culture, religious beliefs, and society's view of autonomy. Nurses emphasise the importance of respecting patients' rights and the importance of education and additional training. There express differing views the on adherence to the "Do Not Resuscitate" order. They also emphasise the need for discussions within interdisciplinary teams, with patients and their families.
Keywords: decision making; end of life; konec življenja; medicinske sestre; nurses; odločanje